PROFIT OPTIMIZATION THROUGH THE IMPLEMENTATION OF JUST IN TIME IN AN EXPEDITION COMPANIES - Uji Barokah; Negina Kencono Putri (The Asia Pacific Journal Of Management Studies, 2024)
Just in Time (JIT) is an inventory management strategy to arrange the delivery of goods to match the production schedule and customer needs. In shipping services, JIT is an inventory control system that regulates the flow of goods so that they can arrive at customers on time. This study aims to determine the description of the application of JIT to optimize profits in expedition companies. The method in this study uses literature studies. The results of the study show that the JIT system provides encouragement for expedition companies to optimize profits through increased efficiency, reduced costs, and improved service quality. These results give the impression for expedition companies to strive to implement the JIT system comprehensively because it can reduce operational costs, efficiency in shipping, improve service quality, reduce waste and risk management, optimize resource use and increase focus on high-value activities so that increased revenues can ultimately optimize profits.